Pengaruh Positive Reinforcement dan Kecemasan Sosial terhadap Keaktifan Belajar Siswa MPLB SMK Negeri di Jakarta Selatan - Safa Putri Nurfitrialin; Santi Susanti; Marsofiyati (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to analyze the influence of positive reinforcement and social anxiety on student learning activity in the Department of Office Management and Business Services (MPLB) at SMK Negeri in the South Jakarta area. The background of this research is based on the importance of creating a conducive learning environment through providing positive reinforcement and the importance of understanding the impact of social anxiety on student participation in the learning process. The method used in this study is a survey method with a quantitative approach. The study population consisted of 360 students spread across three schools. The sampling technique used was proportionate stratified random sampling with an error rate of 5%, so that a sample of 190 students was obtained. Data analysis was carried out using the Structural Equation Modeling (SEM) method based on Partial Least Square (PLS) through the SmartPLS 4.0 application. The analysis consists of three main stages, namely measurement model analysis (outer model), structural model analysis (inner model), and hypothesis testing. The results of the study show that positive reinforcement has a positive and significant effect on student learning activity. This means that the higher the application of positive reinforcement, the more active students are in participating in learning activities. On the other hand, social anxiety has a negative and significant influence on student learning activity. This shows that the higher the level of social anxiety experienced by students, the more active they will be in the learning process. These findings affirm the importance of the role of teachers in implementing learning strategies that encourage active student participation and pay attention to students' psychological aspects such as social anxiety in the teaching and learning process.